2013
DOI: 10.1016/j.crohns.2013.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Presenting features and disease course of pediatric ulcerative colitis

Abstract: Pediatric UC is extensive and severe at the diagnosis, with an overall high rate of disease extension at the follow-up. Endoscopic atypical features are common in young children. The colectomy rate is related to the location and severity of the disease at the diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
51
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 37 publications
8
51
2
2
Order By: Relevance
“…This result is consistent with other paediatric studies: colonic extension was observed in 50% of the 32 cases of UP in the study of Aloi et al , in 65% of the 20 cases of UP in the study of Langholz et al and in 40% of the 38 cases of UP in the study of Hyams et al 6 11 18 In adults (population-based and referral centre studies), colonic extension of UP is less frequent, occurring from 27% to 30% of cases 19 22–30…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result is consistent with other paediatric studies: colonic extension was observed in 50% of the 32 cases of UP in the study of Aloi et al , in 65% of the 20 cases of UP in the study of Langholz et al and in 40% of the 38 cases of UP in the study of Hyams et al 6 11 18 In adults (population-based and referral centre studies), colonic extension of UP is less frequent, occurring from 27% to 30% of cases 19 22–30…”
Section: Discussionsupporting
confidence: 92%
“…The proportion of children with UC presenting with UP at diagnosis in our study (25%) is consistent with another population-based study reporting also 25% of UP,3 a geographically derived incidence cohort from Denmark reporting the same rate of 25% of UP (18) and from a study through a tertiary paediatric gastroenterology centre reporting a rate of 29% 11. The frequency of UP was much lower in other paediatric cohorts performed in gastroenterological centres with, respectively, 10% and 4% 12 18.…”
Section: Discussionsupporting
confidence: 90%
“…Paediatric onset UC is associated with a higher risk for developing ASC episodes, for failing steroid therapy and for colectomy 1114. Numerous predictors have been proposed for evaluating the natural history of paediatric UC but none has been consistently reported across studies,1519 including endoscopic appearance, disease extent15 extraintestinal manifestations,7 serum albumin, weight loss, first degree relative with IBD,17 inflammatory markers and perinuclear antineutrophil cytoplasmic antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Of 110 children with UC in the biologic era, 25% were steroid resistant, 22% were steroid dependent and 5% underwent colectomy 1 year after diagnosis, despite the use of immunomodulators in 40% and infliximab in 15% [4]. Of 62 children with UC who required steroid therapy at diagnosis, 45% were steroid dependent and 5% required colectomy 1 year thereafter [5].…”
Section: The Scope Of the Problemmentioning
confidence: 99%
“…Approximately 25-30% of children with UC will require admission for acute severe colitis (ASC) within 3-4 years from diagnosis, almost twice as often as seen in adult-onset disease [4,6,7]. During these admissions, intravenous steroid failure is noted in 28% of adults and 34% of children, a difference that reaches statistical significance [8,9].…”
Section: The Scope Of the Problemmentioning
confidence: 99%